ANALYSIS OF FACTORS AFFECTING THE LEVEL OF SUCCESS IN BUSINESS DISTRICT TRADERS HANDPHONE KARANGANYAR (Case Study Mobile Traders in the District Karanganyar) - One, Basuni; Lastari, SE.,MM, Siwi (Management, 2010)
This study aims: (1) To determine the effect of capital factor to the success of mobile business merchants in Karanganyar District, (2) To know the influence of business experience to the business mobile phone dealers in Karanganyar, (3) To know the influence of working hours per day on business success mobile traders in Karangnyar, (4) To know the influence of educational level of success of mobile phone dealers in Karanganyar, (5) To know the influence of books on business success in Karanganyar mobile traders. This research type is quantitative, which is a study that aims to obtain proof of a hypothesis, using statistical tests with SPSS. The samples used in this study is to test multiple linear regression (F test), individual linear regression test (t test), test of determination (R2) and classical assumption using a test of autocorrelation, and multicollinearity heterocedastity The results showed together capital factors, work experience, hours worked, education level and bookkeeping factor to the success of mobile phone dealers in the District Karanganyar as evidenced by the value of 20.469> F-table = 2.37, (1) of capital factor has positive and significantly to the success of mobile phone dealers in Karanganyar as evidenced by the large value of t-statistic = 2.58> t-table = 1.671, (2) Work experience has positive and significant impact on the business success of mobile phone dealers in Karanganyar as evidenced by the large t-value statistic = 3.37> t-table = 1.671, (3) Working hours have a positive and significant impact on the success of mobile phone dealers in Karanganyar as evidenced by the large value of t-statistic = 2.47> t-table = 1.671, (4) Level education has positive and significant impact on the business success of mobile phone dealers in Karanganyar as evidenced by the large value of tstatistic = 2.44> t-table = 1.671, (5) Bookkeeping has positive and significant impact on business success in the mobile phone vendors as evidenced by the large Karanganyar value t-statistic = 5.04> t-table = 1.671. Key words: influence of capital, the successful trader, education level